On the notions of Paradigm, Episteme and Epistemological Obstacle (2010)
What relationships can outline between the notions of paradigm, episteme and epistemological obstacle? This text highlights, on the one hand, the epistemological importance of such relationships, and the other hand, tries to suggest how have recourse such